PENINGKATAN PRODUKTIVITAS DAN EFISIENSI PENEBANGAN KAYU MANGIUM DI SATU PERUSAHAAN HUTAN TANAMAN DI PROPINSI JAMBI - Sona Suhartana; Marolop Sinaga; Ishak Sumantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Implementation of felling technique in the timber estate is not yet practiced efficiently and appropriately. Study on the lowest possible felling technique (LPFT) is considered important to increase fellingproductivity and felling efficiency. This study was carried out at a timber estate in iambi in 2003. The aim of this study was to determine the effectof LPFT on fellingproductivity and efficiency.Data collected in this regard were: working time, wood volume, productivity, efficiency, stump height and felling cost. Two-categories data were analyzed with respect to their possible differences using a t-test.Results revealed that implementation of LPFT brought out more convenient impacts in comparison to the conventional felling technique (CFT), as follows: (1) Felling productivity increased at 3.177 m3/hr; (2) felling efficiency increased approximately 7.4%; (3) felling cost decreased by some Rp 159.1; and (4) the average stump height were 21.14 cm for LPFT and 32.83 cmforCFT